Design and fabrication of a flow chamber for the study of cell adhesion and hemocompatibilty in dynamic conditions - Migita, Kevin, author; Popat, Ketul, advisor; Dasi, Lakshmi Prasad, advisor; Prasad, Ashok, committee member (Colorado State University. Libraries, 2011)
Cell adhesion is a well characterized condition of both biomaterial and tissue engineering research. It plays a role in biocompatibility and the proliferation, differentiation and viability of seeded cells. With respect to hemocompatibility, platelet adhesion and subsequent activation is a driving factor in the failure of blood contacting medical devices. Platelets aggregates are vital components in the wound healing and foreign body responses and display various forms of adhesion based on blood flow. However, the study of platelet adhesion on implantable tissue engineering scaffolds under dynamic conditions is very limited, particularly with directional flow. A flow chamber which incorporates a tissue engineering scaffold or functionalized biomaterial was designed and fabricated for investigation of flow patterns and cellular adhesion in response to dynamic conditions on these surfaces. The device utilizes a combination of aspects from both tissue engineering bioreactors and microfluidics platforms to result in a flow chamber which provides the directional flow of a perfused flow bioreactor with the advantages of controlling chamber shape and real time monitoring presented by Polydimethylsiloxane microfluidics chambers. Results of fluid flow study in the chamber modeled for laminar and shear gradient simulated flow show the ability of the device to manipulate flow patterns. Dynamic and static studies of platelet adhesion to poly-(ε-caprolactone) flat and electrospun nanofiber surfaces utilizing the flow chamber provide insight into the hemocompatibility of tissue engineering scaffolds in a dynamic flow setting.
Keywords: chamber; platelets; PCL; flow